2009
DOI: 10.1063/1.3269801
|View full text |Cite
|
Sign up to set email alerts
|

An accurate model potential for alkali neon systems

Abstract: We present a detailed investigation of the ground and lowest excited states of M-Ne dimers, for M=Li, Na, and K. We show that the potential energy curves of these Van der Waals dimers can be obtained accurately by considering the alkali neon systems as one-electron systems. Following previous authors, the model describes the evolution of the alkali valence electron in the combined potentials of the alkali and neon cores by means of core polarization pseudopotentials. The key parameter for an accurate model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…16. It is therefore necessary to compute the electronic structure on the fly to deduce the energy, forces, and couplings, which drive the dynamics.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…16. It is therefore necessary to compute the electronic structure on the fly to deduce the energy, forces, and couplings, which drive the dynamics.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…[14][15][16]19 The whole cluster can therefore be simulated as a one-electron system for which energy, forces, and nonadiabatic couplings can be obtained on the same footing by reasonably cheap computations. The topology of such an intersection is characterized by a seam along which two PES touch each other and the derivatives of the potential energy in the directions perpendicular to the seam do not vanish, in contrast to Renner-Teller intersections.…”
Section: Introductionmentioning
confidence: 99%
“…35,37 However, because dynamical properties often arise due to specific geometric arrangements it is essential to determine and understand the stable structures adopted by those clusters. Ab initio calculations [27][28][29][30][31][32][33] and empirical potentials 13,[19][20][21][22][23][24][25][26] have provided a lot of insight into measured magic numbers by highlighting the dominant contributions to bonding and connecting those contributions to geometric features such as high-symmetry shell completion. Relevant examples for cationic clusters such as Na + Ar n , 20,27 K + Ar n , 21 and Cs + Xe n 21,22 have notably emphasized the importance of the size mismatch between the alkaline ion and the rare-gas atom on the shell occupancy.…”
Section: Introductionmentioning
confidence: 99%
“…Both methods are size consistent, which is important when the number of correlated electrons increases. The computation of the B 2 + PEC was completed by model calculations similar to those used for Ne and Ar 5,[21][22][23] and adapted for Kr. Though not overwhelming, the relativistic effects are not completely negligible for atoms like Kr and Xe.…”
Section: Methodsmentioning
confidence: 99%
“…From a theoretical point of view, numerous model calculation based on CPP approach have been performed. 15,16,[21][22][23] Correlated methods, either configuration interaction or coupled cluster, were used recently for molecules made of Li and light RG. 16,17 Previous theoretical studies of Li-RG reported a large anomalous molecular spin-orbit effect.…”
Section: Introductionmentioning
confidence: 99%